The Pine Branch, February 1928 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the Georgia State Womans College., 1928)
The Pine Branch, February 1928. Periodical magazine. Created and published by the Writers Club of the Georgia State Womans College, Valdosta, Georgia, 1928. Includes: editorials, photographs, poems, short stories, and other writings.
To Jennifer: Mary Kate Burrows | Truthful Gossip: Bessie Young | Brush Strokes: Cora Burghard | Poppies: Hazel Donahue | A Pansy for Thought: Louise Benton | History Repeats Itself: Ila Spooner | Detour: Cora Burghard : | "To Love and Be Loved By Me"?: Lucille Dowling | Editorial: On to College; Be a College Girl! | Y W C A Notes | Society Notes | Athletic Notes | Alumnae Notes | Jokes |
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; Georgia State Womans College; Valdosta; Schools--Georgia; Education